Fibromyalgia Syndrome: A Metabolic Approach Grounded in Biochemistry for the Remission of Symptoms - Lattanzio, Silvia Maria (Frontiers in Medicine, 2017)
Fibromyalgia Syndrome (FMS) is a chronic, complex and heterogeneous disorder of still poorly-understood etiopathophysiology associated with important musculoskeletal widespread pain, fatigue, non-restorative sleep and mood disturbances. It is estimated to afflict 2-3 % of the worldwide population, with clean prevalence among women. The objective of this paper is to propose a novel treatment for symptomatic remission of FMS, grounded in biochemistry and consisting in the withdrawal from the diet of molecules that can indirectly trigger the symptoms. The hypothesis develops from the evidence that low serotonin levels are involved in FMS. Serotonin is synthesized starting from the essential amino-acid tryptophan. The presence of non absorbed molecules in the gut, primarily fructose, reduces tryptophan absorption. Low tryptophan absorption leads to low serotonin synthesis that triggers FMS symptoms. Moreover not-absorbed sugars could also produce a microbiota deterioration activating a positive feedback loop: the increasing microbiota deterioration reduces the functionality of absorption both of fructose and tryptophan in the gut, entering a vicious circle. The therapeutic idea is to sustain serotonin synthesis allowing the proper tryptophan absorption. The core of the cure treatment is the exclusion from the diet of some carbohydrates and the marked reduction of some others. The main target is the limitation of total dietary fructose as marked as possible. It could be an effective strategy to get the remission of symptoms acting on the impaired biochemical pathways. The straying from the treatment is expected to cause the reappear of the symptoms.